Immobilization of lipase in functionalised potassium carrageenan beads and optimization of the enzyme activity - Fauzli, Farah Nabila; Jameel, Ahmad Tariq (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Lipase enzyme is widely used as catalysis for the hydrolysis of fats and lipid to glycerol. It has gained a high demand due to its extensive application as catalyst in variety of other applications such as biosensor development, and food and pharmaceutical industries. However, soluble enzymes in industrial applications encounter difficulty in recovery, as well as the stability and reusability of the enzyme. These limitations can be largely overcome by immobilization of enzymes on suitable solid supports. This research focuses on the immobilization of lipase on the functionalized potassium-carrageenan beads and examined the optimum enzymatic activity using p-nitrophenyl palmitate as substrate. The probable mechanism for immobilization was cross-linking and covalent bonding obtained with the addition of Glutaraldehyde (GA) and Polyethyleneimine (PEI) solution during curing of potassium carrageenan beads. The beads were functionalized by treatment with Glutaraldehyde (GA) and Polyethyleneimine (PEI) prior to immobilization. The effects of enzyme concentration, curing time, temperature and pH values on the enzyme loading and enzymatic activity were studied. The maximum enzyme loading was obtained at 1 hour curing time and 50mg/mL lipase concentration. The maximum lipase activity was found at 35⁰C and pH 8.